Management of Financial Administration in the General Bureau of Regional Secretariat North Sulawesi Province in the Digital Era - Koroh, Yovano Elisa; Sendouw, Recky HE; Mamonto, Fitri H. (International Journal of Information Technology and Education, 2022)
Regulation Government Number 12 of 2019 Concerning Management Regional Finance also mentions management finance area is whole activities that include planning and budgeting, implementation and administration, reporting and accountability, as well supervision finance area. The purpose of this research is to analyze and describe management administration finance at the General Bureau Regional Secretariat of North Sulawesi Province. The type of research used in this study is descriptive qualitative and the collection technique is by observation, interviews and documentation. Informants in this study are a) Head of the General Bureau Regional Secretariat of North Sulawesi Province, b) Head of Sub-Division of Accounting and Administration of Regional Assets of the General Bureau Regional Secretariat North Sulawesi Province, c) Head Field Planning, Control and Evaluation of Regional Development Bapeda of North Sulawesi Province, and d) Treasurer expenditure General Bureau Regional Secretariat North Sulawesi Province. In general, the results of this research are 1) The management of financial administration at the General Bureau of the Regional Secretariat of North Sulawesi Province has not been effective in accordance with Government Regulation Number 12 of 2019 Concerning Regional Financial Management, this is based on research results that it is known that out of 4 (four) aspects of management financial administration is only the reporting and accountability aspects that have been running effectively while the other 3 (three) aspects are a) Planning and budgeting, b) Implementation and administration , and c) Supervision has not been running effectively , 2) Inhibiting factors management of financial administration at the General Bureau of the Regional Secretariat of North Sulawesi Province are: a) Lack of knowledge of the Head of Finance and Verification Subdivision and lack of accuracy and thoroughness of TAPD b) Limited HR of the Regional Government Budget Team, namely from the North Sulawesi Province Regional Finance and Assets Agency and the North Sulawesi Provincial Bappeda, as well as limited human resources working at the North Sulawesi Provincial Inspectorate (PPUD and Auditor) c) Inadequate financial administration management facilities where the internet connection network system is weak in SIMDA North Sulawesi Province, d) The last inhibiting factor is the low performance of human resources, namely slowness in collecting worksheets , inaccuracy of spending treasurers and PPK, low time discipline of financial managers in issuance, SPD and SP2D finalization